Weed Flora and Their Ethnobotanical Importance at Daffodil International University Campus, Bangladesh (Journal of the Bangladesh Agricultural University, 2025)
This study documented the weed flora and their ethnobotanical importance within the Daffodil International University (DIU) campus, Bangladesh. Field surveys were conducted across seven habitat categories between July 2024 and February 2025. A total of 55 species belonging to 50 genera and 16 families were recorded, with Asteraceae (18 spp.) and Poaceae (14 spp.) as the most represented families. More than half of the flora were perennials (54.5%), while annuals accounted for 38.2%. Several species were cosmopolitan and widely distributed, including Cyperus rotundus, Cynodon dactylon, and Ipomoea aquatica. Ethnobotanical review revealed that most of the species have recognized uses. Prominent examples include Eclipta alba (hair growth and wound healing), Ageratum conyzoides (skin disorder), Cyanthillium cinereum (smoking cessation aid), Panicum repens (fodder) and Ipomoea aquatica (nutritious leafy vegetable). The findings underscore the ecological resilience and cultural relevance of weeds in managed landscapes.J Bangladesh Agril Univ 23(4): 498–507, 2025